Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-23605-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus fertilization consistently favor pathogenic over mutualistic fungi in grassland soils

Abstract: Ecosystems across the globe receive elevated inputs of nutrients, but the consequences of this for soil fungal guilds that mediate key ecosystem functions remain unclear. We find that nitrogen and phosphorus addition to 25 grasslands distributed across four continents promotes the relative abundance of fungal pathogens, suppresses mutualists, but does not affect saprotrophs. Structural equation models suggest that responses are often indirect and primarily mediated by nutrient-induced shifts in plant communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 74 publications
9
95
2
Order By: Relevance
“…Along the continuum, if the symbiont can obtain benefits from the host at no cost in the absence of any enemies, then this microbe is on course toward a parasitic lifestyle (Vorburger and Gouskov, 2011). Notably, the degree of damage incurred by the host and the extent of resource acquisition could be intensified depending on a nutritious environment for pathogens and driven by a great selection pressure to propagate given the limited life span of the microbe (Rafaluk-Mohr, 2019;Lekberg et al, 2021). Once the microbe overcomes all the defense barriers in its host plant, thus, putting the host into disease state, it is usually called a pathogen.…”
Section: Pathogenesismentioning
confidence: 99%
“…Along the continuum, if the symbiont can obtain benefits from the host at no cost in the absence of any enemies, then this microbe is on course toward a parasitic lifestyle (Vorburger and Gouskov, 2011). Notably, the degree of damage incurred by the host and the extent of resource acquisition could be intensified depending on a nutritious environment for pathogens and driven by a great selection pressure to propagate given the limited life span of the microbe (Rafaluk-Mohr, 2019;Lekberg et al, 2021). Once the microbe overcomes all the defense barriers in its host plant, thus, putting the host into disease state, it is usually called a pathogen.…”
Section: Pathogenesismentioning
confidence: 99%
“…Physico-chemical properties, such as soil pH, nutrient availability, soil moisture and temperature, among different soil types or along biogeographical distance patterns shape the structure of the soil microbial community [21] , [22] , [23] , [24] , which determines the initiation of rhizosphere community assembly. In particular, anthropogenic activities, generally agricultural management practices, have profound impacts on the physico-chemical properties of the soil, consequently influencing the soil and the rhizosphere microbial community [25] , [26] . Amplicon sequencing-based studies focusing on the rhizosphere microbial communities of different A. thaliana populations have demonstrated that soil type is the primary driving factor affecting the rhizosphere bacterial community [15] ; however, climate is more important for the rhizosphere fungal community than soil type [27] .…”
Section: Factors Driving the Assembly Of The Rhizosphere Microbiomementioning
confidence: 99%
“…or particular functional groups, such as grasses (De Schrijver et al, 2011). Eutrophication can also shift growth relative to defence in individual plants (Stamp, 2003) or increase soil pathogens relative to mutualists (Lekberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%